HUBUNGAN TINGKAT PENGETAHUAN TENTANG PERSONAL HYGIENE TERHADAP PERILAKU REMAJA PUTRI SAAT MENSTRUASI - Raissy Amallya Faj'ri; Sunirah; Fauziah H Wada (Jurnal Ilmiah Keperawatan IMELDA, 2022)
Adolescent girls are susceptible to infection of reproductive organs caused by inappropriate behavior in maintaining personal hygiene, especially during menstruation (Handayani, 2018). Some teenagers do not know how to do personal hygiene during menstruation that is good and right, when to change sanitary napkins, and how to wash sanitary napkins (Dewi A.L, 2014), this is due to the lack of information that teenagers get. The phenomenon of menstrual hygiene practices in adolescents is still relatively low. Aim: to determine the relationship between the level of knowledge about personal hygiene and the behavior of adolescent girls during menstruation. Methods: This research is a quantitative with descriptive correlation. The design of this study used a cross sectional approach. . The number of research samples is 113 students women in the SMP IT Assu’adaa. The sampling technique used was purposive sampling. Data analysis technique using Chi-square. Results: showed that the majority of respondents had poor personal hygiene knowledge as many as 65 respondents (57.5%), while most respondents had poor personal hygiene behavior as many as 59 respondents (52.2%). There is a significant relationship between knowledge of personal hygiene and hygiene behavior of adolescent girls during menstruation (p value = 0.002). Conclusion: adolescent girls who have poor personal hygiene knowledge are likely to have poor hygiene behavior during menstruation. Suggestion: teenagers are expected to start looking for information about good personal hygiene during menstruation. and parents and health workers can provide information related to this, so that hygiene behavior during menstruation can be carried out properly and correctly.